Exposure to polychlorinated biphenyls (PCBs) affects the histology and antioxidant capability of the clam Cyclina sinensis - Liu, Meimei; Fan, Sishao; Rong, Zhichao; Qiu, Hao; Yan, Susu; Ni, Hongwei; Dong, Zhiguo (Frontiers in Marine Science, 2023)
Polychlorinated biphenyls (PCBs) are environmentally persistent and highly toxic organochlorine compounds that may cause toxic effects on aquatic animals. In this study we assess the toxic effect of PCBs on a bivalve used in aquaculture, the clam Cyclina sinensis. To this end, individuals of C. sinensis were exposed for 72 h at two PCB concentrations (1 ng/L and 10 ng/L) and control (absence of PCBs). At the end of the exposure, the hemolymph, hepatopancreas, and gills samples of C. sinensis were harvested for analysis of the enzyme activity and histology. The results showed that acute PCBs exposure decreased the survival rate of C. sinensis compared to the control. Acute PCBs exposure up-regulated the enzymatic activity of superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) and the content of malondialdehyde (MDA) in the hemolymph of C. sinensis, while down-regulated the non-specific enzymatic activity of alkaline phosphatase (AKP). For the hepatopancreas, 1 ng/L PCBs exposure up-regulated the enzymatic activity of SOD while down-regulated the enzymatic activity of CAT of C. sinensis. In the gill, the enzymatic activity of CAT decreased significantly and the MDA content increased of C. sinensis after 10 ng/L PCBs exposure. Moreover, histological observations showed that acute exposure to PCBs caused loss of gill filaments and lateral cilia and shortening of their length, in the studied organism. The present study will provide valuable reference data for marine shellfish aquaculture and toxicology research.